2013
DOI: 10.1186/1752-1947-7-86
|View full text |Cite
|
Sign up to set email alerts
|

A supratentorial primitive neuroectodermal tumor presenting with intracranial hemorrhage in a 42-year-old man: a case report and review of the literature

Abstract: IntroductionWe report on a very rare case of a supratentorial primitive neuroectodermal tumor in an adult, which presented with intracerebral hemorrhage, and review the relevant medical literature.Case presentationA 42-year-old Caucasian man complained of a sudden headache and nausea-vomiting. The patient rapidly deteriorated to coma. An emergency computed tomography scan showed an extensive intraparenchymal hemorrhage that caused significant mass effect and tonsilar herniation. During surgery, an increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…The clinical manifestations are associated with the site of the tumor, which is often characterized by high cranial pressure, and may be associated with epilepsy, abnormal mental disorders, and mild hemiplegia. [ 6 , 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations are associated with the site of the tumor, which is often characterized by high cranial pressure, and may be associated with epilepsy, abnormal mental disorders, and mild hemiplegia. [ 6 , 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the difficulties in treating GBM-PNET, radiographic presentation varies considerably and imaging characteristics are not fully understood. Though there reports of PNET presenting as intracranial hemorrhage (ICH) are rare,[ 8 ] this is the first writing of a patient with initially diagnosed and treated GBM-PNET presenting as a PNET-only subdural recurrence. Special interest has been placed on utilizing DWI sequencing when suspicion for GBM-PNET occurrence is elevated as restricted diffusion in discrete regions can elucidate to PNET-like components.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 9 10 11 ] Variants retaining foci of variable histology are recognized and are usually cited as single case reports. [ 4 6 8 ] The etiology of these tumors with distinct areas of sarcoma or primitive neuroectodermal tumor (PNET) is unknown; existing literature suggest that discrete foci of cellularity arise in pre-existing glioma. [ 9 ] Of interest, these lesions can present with radiographic features deviating from the contemporary glioblastoma on magnetic resonance imaging (MRI), thus pointing towards a variant form.…”
Section: Introductionmentioning
confidence: 99%
“…These tumors have a high proliferation rate and often disseminate to the cerebrospinal fluid requiring craniospinal radiation combined with platinum-based chemotherapy. PNETs carry a poor prognosis similar to glioblastoma multiforme, but often have a more robust response to therapy [ 3 ]. Kim, et al reported a 75% three-year mean survival in their series of adult patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%